Technical Review of The Role Physical Conditions in Football - Firmansyah, Awang; Prasetya, Reza Aziz; Ardha, Muchamad Arif Al (Faculty of Sport and Health Sciences, 2021)
Football requires good physical condition in playing and competing. There are four phases in football training, namely physical, technical, tactical and mental. This study discusses the physical conditions required in the sport of football and was analyzed using the review method against references published online, related to physical conditions. In this research, it shows that the physical components in football are very influential in the game. Limited this study does not analyze matches. Research related to physical components has been widely used such as strength, flexibility, speed, endurance and anthopometric conditions, namely arm length, leg length.